Pengembangan Media Pembelajaran Berbasis E-Learning Menggunakan Chamilo di SMAN 13 Padang - Nurkhofifah Nurkhofifah; Loli Setriani; Ade Irma Suryani (STKIP PGRI Sumatera Barat, 2022)
The development of E-Learning-Based Learning Media Using Chamilo at SMA Negeri 13 Padang was motivated by the lack of use of e-learning learning media in the teaching and learning process.The purpose of this study was to determine the results of expert validation, teacher responses, student responses and the practicality of media at SMA Negeri 13 Padang. The research method used is Research and Development (R&D). The subjects in this study were students of class XI IPS SMA Negeri 13 Padang. The data analysis technique used in this research is validation analysis using ICC, Teacher Response, Student Response and Practicality.The results of the study show that: 1.) Making e-learning learning media using chamilo includes validation by experts in the fields of media, education, information technology and language. In order to obtain media validation data and process it using the Intereclass Coefficient Correlation (ICC) formula assisted by the SPSS program, the result is 0.934. If the result is more than 0.50, the validation level is considered appropriate. 2.) The results of the geography teacher's response at SMA Negeri 13 Padang are expressed in terms of an average score of 94% belonging to the very interested category. 3.) The results of student responses in the small group trial obtained an average percentage of 77% while in the large group trial the average percentage was 77.5%. 4.) and the practicality of the media obtained a percentage score of 88% with the category